Relación entre la helmintiasis intestinal y el estado nutricional-hematológico en niños de una escuela rural en el estado Sucre, Venezuela - Figuera Lourdes; Kalale Heidi; Marchán Edgar (Kasmera, 2006)
Abstract: A parasitological, nutritional and hematological evaluation was carried out on 103 children of both sexes between 4-12 years of age from a rural school at Santa Fe, Sucre state, Venezuela, from January-March 2003. Fecal samples were analyzed using a fresh test, Willis Malloy, and the quantitative Kato-Katz method. Nutritional status was determined by anthropometric indexes combinations. Haematological parameters were evaluated by classical methods and the degree of eosinophilia was expressed in absolute eosinophil counts. Exactly 93.2% of schoolchildren were found to have parasites with high poliparasitism (83.3%). Intestinal helminths prevalence was 82.5%, highlighted by 69.4% of Trichuris trichiura and Ascaris lumbricoides association, with a predominant light intensity of infestation. Around 91.2% (31/34) of individuals with malnutrition presented helminthiasis. Eosinophilia was found in 97.6% of schoolchildren infested by helminths (p< 0,001). And 83.3% (20/24) were infested by helminths in the group of children with anemia (23.3%). About 88.8% of children with intestinal helminthiasis belonged to the VTH level socioeconomic stratum. These findings suggest that the school population evaluated lives in a high helminth hyperendemic area, consistent with the socioeconomic stratum found. Additionally, it was established that eosinophilia in these schoolchildren is a factor associated with intestinal helminthiasis.